2014
DOI: 10.1111/dme.12478
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex on renal function decline in people with Type 2 diabetes

Abstract: Male sex is an important independent factor associated with renal function decline in Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 25 publications
6
61
1
Order By: Relevance
“…Yet, despite considerable research efforts, the pathophysiological mechanisms of DN are poorly understood and effective treatments are still lacking. Over recent years, the results of basic and clinical studies have indicated a gender-related decline of renal function in type 2 diabetes mellitus (T2DM), with male gender considered a risk factor [4,5]. In line with this assumption are observations in male patients with type 1 diabetes mellitus (T1DM), in whom DN rarely appears before puberty, thereby supporting the hypothesis of a negative role of testosterone (T) [6].…”
Section: Introductionmentioning
confidence: 84%
“…Yet, despite considerable research efforts, the pathophysiological mechanisms of DN are poorly understood and effective treatments are still lacking. Over recent years, the results of basic and clinical studies have indicated a gender-related decline of renal function in type 2 diabetes mellitus (T2DM), with male gender considered a risk factor [4,5]. In line with this assumption are observations in male patients with type 1 diabetes mellitus (T1DM), in whom DN rarely appears before puberty, thereby supporting the hypothesis of a negative role of testosterone (T) [6].…”
Section: Introductionmentioning
confidence: 84%
“…In non-diabetic individuals with chronic kidney disease, male sex has been identified as a risk factor for rapid decline in renal function as opposed to pre-menopausal women [17]. In diabetic individuals conflicting reports exist in different populations; a recent study among Japanese subjects with type 2 diabetes identified a higher risk in women [18], whereas a report regarding European individuals indicated an increased risk for renal decline in men [19]. Thus, the influence of sex on the development of DN has yet to be established conclusively [16, 2023].…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in CKD progression are influenced by various risk factors such as hypertension, [12,13] hyperglycemia, [14] albuminuria, [15] dyslipidemia, [16] body mass index, [17,18] lifestyle factors, [19,20] and renal structure and sex hormones. [21] Duru et al [12] demonstrated that African-American men have a higher risk of CKD progression than African-American women do because of the poorly controlled hypertension among these males.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Albuminuria incidence and decreases in the eGFR might be greater among men with diabetes than among women with diabetes. [14,15,22] …”
Section: Introductionmentioning
confidence: 99%